PERKEMBANGAN INFRASTRUKTUR PENGISIAN BATERAI KENDARAAN LISTRIK DI INDONESIA - I. P. Dharmawan; I. N. S. Kumara; I. N. Budiastra (Program Studi Teknik Elektro UNUD, 2021)
The development of electric vehicles in Indonesia started after the issuance ofPresidential Decree 55/2019 about battery-based eletric vehicles. The development of electricvehicles must be supported with the charging infrastructure so users do not experienceproblems in charging the vehicles and therefore more people will switch to electric vehicle. Thispaper discusses the current status of charging infrastructure for electric vehicle in Indonesia.Currently, there are several type of vehicle charging facilites consist of 7.000 public electriccharging station or SPLU, 97 public electric vehicle charging station or SPKLU, 9 public electricvehicle battery exchange station or SPBKLU distributed across Sumatra, Java, Bali, NTB,Sulawsi and Kalimantan. In the case of Bali, there are 166 of SPLU, 5 of SPKLU, and there isno SPBKLU yet. The total accumulative energy consumed through the charging stations in Baliis 169.481 kWh. The figure is low due to lack of information about the charging station and thefact that the number of electric vehicles in Bali is still low.